2005
DOI: 10.1016/j.ydbio.2005.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Uroplakin III, a novel Src substrate in Xenopus egg rafts, is a target for sperm protease essential for fertilization

Abstract: In a previous study, we identified Xenopus egg uroplakin III (xUPIII), a single-transmembrane protein that localized to lipid/membrane rafts and was tyrosine-phosphorylated upon fertilization. An antibody against the xUPIII extracellular domain abolishes fertilization, suggesting that xUPIII acts not only as tyrosine kinase substrate but also as a receptor for sperm. Previously, it has been shown that the protease cathepsin B can promote a transient Ca2+ release and egg activation as seen in fertilized eggs (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 58 publications
4
47
1
Order By: Relevance
“…Nonetheless, research has found that Src-family kinases (SFKs) and phospholipase Cg (PLCg) are involved in the activation of the phosphoinositide pathway and production of inositol 1,4,5-trisphosphate (IP 3 ) during fertilization in sea urchins, starfish, and frogs, which reflects the contribution of a plasma membrane receptor/signaling complex (Giusti et al 1999;Sato et al 2000). Remarkably, a receptor responsible for recruiting and activating SFKs during fertilization remains undiscovered (Mahbub Hasan et al 2005). Similarly, it has proved difficult to uncover how the sperm initiates oscillations.…”
mentioning
confidence: 99%
“…Nonetheless, research has found that Src-family kinases (SFKs) and phospholipase Cg (PLCg) are involved in the activation of the phosphoinositide pathway and production of inositol 1,4,5-trisphosphate (IP 3 ) during fertilization in sea urchins, starfish, and frogs, which reflects the contribution of a plasma membrane receptor/signaling complex (Giusti et al 1999;Sato et al 2000). Remarkably, a receptor responsible for recruiting and activating SFKs during fertilization remains undiscovered (Mahbub Hasan et al 2005). Similarly, it has proved difficult to uncover how the sperm initiates oscillations.…”
mentioning
confidence: 99%
“…In that paper, we showed data about chromatographic fractionation of membrane-associated proteins and in vitro protein kinase assay, by which we could detect an elevation of the activity of xSrc in response to fertilization. Our further studies demonstrated that pharmacological (e.g., use of inhibitors; Sato et al 1999Sato et al , 2000Sato et al , 2001 or molecular biological inhibition of xSrc (i.e., expression of kinase-negative mutant of xSrc; manuscript in preparation) impairs the ability of Xenopus eggs to undergo calcium reactions and egg activation in response to sperm and that Xenopus eggs can be activated in a Src-dependent manner by artifi cial egg activators that interacts with the egg surface (i.e., RGD peptide and cathepsin B; Sato et al 1999 ;Mahbub Hasan et al 2005 ) and by hydrogen peroxide that may directly activate xSrc (Sato et al 2001 ). These results suggest that xSrc acts between gamete interaction/fusion and an increase in intracellular calcium concentration at fertilization ( Fig.…”
Section: Characterization Of Src As a Mediator Of Gamete Interaction mentioning
confidence: 99%
“…The fi rst subproject is to identify novel fertilization-related components by characterization of MDs-associated molecules. A major achievement in this subproject is the identifi cation of a type I transmembrane protein uroplakin III (UPIII) that is thought to be involved in gamete interaction, In this project, iEMD are subjected to in vitro treatment with sperm, cathepsin B, Src, or some others, and analyzed for their biochemical (e.g., tyrosine phosphorylation of MDsassociated proteins) as well as cell biological responses (e.g., ability of the sperm to fertilize eggs) which may involve the action of sperm-derived protease, and regulation of xSrc activity, in that UPIII may be involved in the negative regulation of xSrc in unfertilized eggs (Mahbub Hasan et al 2005, 2007Mammadova et al 2009 ;Sakakibara et al 2005a ) (Fig. 14.1 ).…”
Section: Discovery Of Egg Mds As An Important Resource For Fertilizatmentioning
confidence: 99%
“…lymphocyte activation, neuronal signal transduction). In some sea invertebrates (sea urchin, starfish, ascidian, and others) (Abassi et al 2000;Belton et al 2001;Dasgupta and Garbers 1983;Giusti et al 1999a;Giusti et al 1999b;Giusti et al 2000a;Giusti et al 2003;Giusti et al 2000b;Kamel et al 1986;O'Neill et al 2004;Runft et al 2004;Runft and Jaffe 2000;Runft et al 2002;Sakuma et al 1997;Shen et al 1999;Shilling et al 1994;Stricker et al 2010a;Townley et al 2006;Townley et al 2009), fish (zebrafish) (in this case, Fyn tyrosine kinase) and frog (African clawed frog) (Glahn et al 1999;Iwasaki et al 2008;Iwasaki et al 2006;Kushima et al 2011;Mahbub Hasan et al 2011;Mahbub Hasan et al 2007;Mahbub Hasan et al 2005;Mammadova et al 2009;Sakakibara et al 2005;Sato et al 1996;Sato et al 2006a;Sato et al 1999;Sato et al 2004;Sato et al 2002;Sato et al 2001;Sato et al 2003;Sato et al 2000;Sato et al 2006b;Steele 1985;Steele et al 1989b;…”
Section: Src Tyrosine Kinase (Src)mentioning
confidence: 99%